Identification of candidate genes for leaf size by QTL mapping and transcriptome sequencing in Brassica napus L - Fengjie Cheng; Yuwen Wang; Aoyi Peng; Shuyu Li; Jun Chen; Xiaoxiao Zheng; Jie Xiong; Ge Ding; Bingchao Zhang; Wen Zhai; Laiqiang Song; Wenliang Wei; et al. (BMC Genomics)
Abstract Leaf is the main photosynthetic organ at the seedling stage of rapeseed and leaf size is a crucial agronomic trait affecting rapeseed yield. Understanding the genetic mechanisms underlying leaf size is therefore important for rapeseed breeding. In this study, QTL mapping for three traits related to leaf size, i.e., leaf width (LW), leaf length (LL) and leaf area (LA), was performed using a recombinant inbred line (RIL) population and four QTLs for LW, two QTLs for LL and four QTLs for LA were detected. Transcriptome analysis revealed that differentially expressed genes (DEGs) were enriched in the GO terms related to microtubules, and the expression level of several genes involved in cell division also showed significant differences. Microscopic analysis suggested that the cell number was the main factor regulating leaf size. Combining QTL mapping and RNA sequencing, four promising candidate genes, including BnaA10G0085600ZS, BnaA10G0156900ZS, BnaC03G0441700ZS, and BnaC08G0410600ZS, were proposed to control leaf size by regulating cell division. The results of QTL, transcriptome analysis, and anatomical observation were highly consistent, collectively revealing that genes related to cell division played a crucial role in regulating the leaf size traits in rapeseed. These findings provided further insights into the genetic mechanism of leaf size and built fundamental theory basis for high-density tolerance breeding in rapeseed.